Логарифмічна похідна і кутова щільність нулів цілої функції нульового порядку - Заболоцький, М.В.; Мостова, М.Р. (Український математичний журнал, 2014)
Для целых функций нулевого порядка установлена связь между угловой плотностью нулей, асимптотикой логарифмической производной и регулярным ростом ее коэффициентов Фурье. For an entire function of zero order, we establish the relationship between the angular density of zeros, the asymptotics of logarithmic derivative, and the regular growth of its Fourier coefficients.